Shrinking cities in Romania. Orase românesti în declin. Vol. 2: Responses and interventions. Reactii si interventii. - (:unkn) unknown (DOM Publ., 2019)
The very substantial and precise study (Volume 1) provides a deep understanding of the shrinking cities phenomenon. Volume 2 goes one important step further, by daring to formulate and initiate constructive ways to address these issues and envisioning perspectives for these marginalized places.
Keywords: Stadtentwicklung; Schrumpfung; Problemraum; Intervention; Stadtsanierung; Stadterneuerung; Gebäude; Nachnutzung; Postsozialismus